Photovoltaic performance analysis using Computational Fluid Dynamics (CFD) simulation methods - A. Syahrinaldy Syahruddin; Radhiansyah; Marfiansyah Nasra Dwiprayuda (University of Muhammadiyah Malang, 2025)
Photovoltaic technology is increasingly in demand by the wider community. Situated in the tropics, Indonesia benefits from abundant sunlight, positioning it favourably for the adoption of this technology. Studies on photovoltaics have been conducted in potential areas, including Parepare, South Sulawesi. As one of the South Sulawesi regions with strong agricultural and industrial potential, it is currently pursuing sustainable renewable energy development, encompassing photovoltaic technology. This study aims to examine the performance of solar photovoltaic systems through Computational Fluid Dynamics (CFD) simulations. The solar photovoltaic system is modelled and simulated using fluid-flow simulation software. ANSYS Fluent Student is applied with a constant solar radiation of 800 V/m2 for an hour. Experimental test data serve as a reference for simulation in this study. The results indicate that the maximum temperature ranged from 47.7 °C to 50 °C, represented by an orange-to-red colour gradient in the temperature contour, while the minimum temperature ranged from 26.9 °C to 31 °C, represented by a dark-to-light blue gradient. This suggests that the one-hour heating process under constant solar radiation, as simulated by this method, operates effectively and more accurately reflects real-world conditions.